Teachers' Adoption of Inquiry-Based Learning Activities: The Importance of Beliefs About Education, the Self, and the Context. (November 2019) - Voet, Michiel; De Wever, Bram
Even though studies have shown that the impact of professional development on inquiry-based learning (IBL) tends to remain limited when it fails to consider teachers' beliefs, there is little known about how these beliefs influence teachers' adoption of IBL. In answer to this issue, the present study offers a framework that explains teachers' use of IBL through three constitutive dimensions of beliefs systems, covering the constructs of education, the self, and the context. This framework is empirically investigated through a survey study with 536 secondary school history teachers. The resulting data are used to estimate a structural equation model (SEM), which indicates that the framework is able to explain a relatively large portion (38%) of the variance in teachers' decision to implement IBL. Based on the findings, the implications for professional development and research on teachers' use of IBL in general, and within history education in particular, are discussed.